Recent advances in ion‐sensitive field‐effect transistors for biosensing applications - Xiaohao Ma; Ruiheng Peng; Wei Mao; Yuanjing Lin; Hao Yu (Electrochemical Science Advances, 2023)
Abstract Over the past decades, considerable development and improvement can be observed in the area of the ion‐sensitive field‐effect transistor (ISFET) for biosensing applications. The mature semiconductor industry provides a solid foundation for the commercialization of the ISFET‐based sensors and extensive research has been conducted to improve the performance of ISFET, with a special research focus on the materials, device structures, and readout topologies. In this review, the basic theories and mechanisms of ISFET are first introduced. Research on ISFET gate materials is reviewed, followed by a summary of typical gate structures and signal readout methods for the ISFET sensing system. After that, a variety of biosensing applications including ions, deoxyribonucleic acid, proteins, and microbes are presented. Finally, the prospects and challenges of the ISFET‐based biosensors are discussed.